2007
DOI: 10.2320/matertrans.mrp2007161
|View full text |Cite
|
Sign up to set email alerts
|

Cu<SUB>45</SUB>Zr<SUB>45</SUB>Al<SUB>5</SUB>Ag<SUB>5</SUB> Bulk Glassy Alloy with Enhanced Compressive Strength and Plasticity at Cryogenic Temperature

Abstract: Compressive tests were made for the as-cast Cu 45 Zr 45 Al 5 Ag 5 bulk glassy alloy rods with a diameter of 3 mm at 298 and 77 K, at an initial strain rate of 5 Â 10 À4 s À1 . It was found that at 77 K, the compressive yield strength, maximum strength and plastic strain to fracture of the glassy alloy rod are higher than those at 298 K. The maximum strength measured at 77 K is about 13% larger than that measured at 298 K. In particular, its plasticity at 77 K is significantly enhanced. SEM observations reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
2
16
2
Order By: Relevance
“…We also noticed the inconsistency between the reported enhanced compressive plasticity [1][2][3][4][5][6][7][8] and the reduced bending plasticity presented here in a certain range of cryogenic temperature. The enhanced compressive plasticity is generally believed to result from an intrinsic shear-band nucleation rate that increases with decreasing temperature [1,5,7].…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…We also noticed the inconsistency between the reported enhanced compressive plasticity [1][2][3][4][5][6][7][8] and the reduced bending plasticity presented here in a certain range of cryogenic temperature. The enhanced compressive plasticity is generally believed to result from an intrinsic shear-band nucleation rate that increases with decreasing temperature [1,5,7].…”
Section: Discussioncontrasting
confidence: 42%
“…On the other hand, the strengthened materials at low temperature usually behave more brittle. However, very interestingly, it is reported that BMGs at cryogenic temperature show enhanced plasticity in compression [1][2][3][4][5][6][7][8], even in tension [9,10]. Such plasticity improvement was attributed to multiple-nucleation of shear bands at low temperature [1,5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 225 at 77 K might also be ascribed to the decrease of the STZ volume due to low temperature, where nano-scaled "chevron" patterns rather than vein patterns on the low temperature fracture surface indicate an apparent decrease in the plasticity [7]. While for other BMGs [49][50][51][52][53][54][55] with both enhancements of yield strength and plasticity under compression when the test temperatures decrease from room temperature to liquid nitrogen temperature (77 K), a lower test temperature might introduce a brittle failure, i.e. ductile-to-brittle transition.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Consequently, we performed compression tests at cryogenic temperatures and at various strain rates using Cu 45 Zr 45 Al 5 Ag 5 , Zr 55 Al 10 Ni 5 Cu 30 and Ni 60 Pd 20 P 17 B 3 BGA samples. [17][18][19] It was found that the compressive maximum strength and plastic strain prior to failure are higher at cryogenic temperatures than at ambient temperature. Recently, Huang et al 20) reported similar results in compression tests for a Ti 40 Zr 25 Ni 3 Cu 12 Be 20 BGA.…”
Section: Introductionmentioning
confidence: 99%